2019
DOI: 10.1002/jcb.29353
|View full text |Cite
|
Sign up to set email alerts
|

NCAM regulates the proliferation, apoptosis, autophagy, EMT, and migration of human melanoma cells via the Src/Akt/mTOR/cofilin signaling pathway

Abstract: The neural cell adhesion molecule (NCAM) plays critical roles in multiple cellular processes in neural cells, mesenchymal stem cells, and various cancer cells. However, the effect and mechanism of NCAM in human melanoma cells are still unclear. In this study, we found that NCAM regulated the proliferation, apoptosis, autophagy, migration, and epithelial‐to‐mesenchymal transition of human melanoma cells by determining the biological behavior of NCAM knockdown A375 and M102 human melanoma cells. Further studies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 55 publications
2
32
0
Order By: Relevance
“…Therefore, the decrease in CFL1 expression after treatment of NJXA mainly destroyed the balance between F-actin and G-actin, which then further inhibited the cancer metastasis. Actin cytoskeleton not only plays an important role in cell migration, which has also been reported to regulate EMT in metastatic cancer (Shankar and Nabi, 2015;Li et al, 2020). Our study here also found that after treatment with NJXA, the expression of EMT markers was down regulated, such as snail and vimentin, while E-cadherin was up regulated (Supplementary Figure 6).…”
Section: Cfl1-mediated Dynamics Of Actin Cytoskeleton Is Involved In supporting
confidence: 80%
See 1 more Smart Citation
“…Therefore, the decrease in CFL1 expression after treatment of NJXA mainly destroyed the balance between F-actin and G-actin, which then further inhibited the cancer metastasis. Actin cytoskeleton not only plays an important role in cell migration, which has also been reported to regulate EMT in metastatic cancer (Shankar and Nabi, 2015;Li et al, 2020). Our study here also found that after treatment with NJXA, the expression of EMT markers was down regulated, such as snail and vimentin, while E-cadherin was up regulated (Supplementary Figure 6).…”
Section: Cfl1-mediated Dynamics Of Actin Cytoskeleton Is Involved In supporting
confidence: 80%
“…It is well known that the inhibition of LIM kinase 1 downregulated CFL1 phosphorylation, which then suppresses the motility of cancer cells (Lu et al, 2018). Recently, research found that the inactivation of the Src/Akt/mTOR pathway could also suppress the phosphorylation of CFL1, which then regulate the migration and EMT (Li et al, 2020;Kulkarni et al, 2021). It has been reported that induction of EMT promotes invasion and migration of cancer cells, and predicts poor prognosis in HCC patients (Wang G. et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…The molecular mechanism might be associated with the redistribution of the TJ proteins ZO-1, occludin, and claudin-1 in cells caused by the caveolae-mediated endocytosis of TJ components. Other studies have revealed that several signaling pathways were involved in the cofilin-dependent actin homeostasis, such as EGFR/Src/Akt and RhoA/ROCK pathway (Li et al, 2019; Xue et al, 2019). In addition, work in cultured cells has uncovered the mechanism and regulation of actin-mediated TJ, including Arp2/3 complex (Kang et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that lncRNA HULC may enhance the HIP-1αrelated PI3K/AKT/mTOR signaling, which cross-talks with the Wnt/β-catenin signaling to upregulate TGF-β and Snail expression, promoting the EMT process in GBM cells. [21][22][23] We are interested in further investigating the molecular mechanisms by which lncRNA HULC regulates the process of EMT and VM in GBM.…”
Section: Discussionmentioning
confidence: 99%